Novel amides of 1, 1‐bis‐(carboxymethylthio)‐1‐arylethanes: Synthesis, characterization, acetylcholinesterase, butyrylcholinesterase, and carbonic anhydrase inhibitory properties. Issue 9 (10th July 2018) - Taslimi, Parham; Osmanova, Sabiya; Caglayan, Cuneyt; Turkan, Fikret; Sardarova, Sabira; Farzaliyev, Vagif; Sujayev, Afsun; Sadeghian, Nastaran; Gulçin, İlhami
Abstract: The thiolation reaction was carried out in a benzene solution at 80°C and p ‐substituted ketones and mercaptoacetic acid in a molar ratio (1:4) of in the presence of a catalytic amount of toluene sulfonic acids. The enzyme inhibition activities of the novel amides of 1, 1‐bis‐(carboxymethylthio)‐1‐arylethanes derivatives were investigated. These novel amides of 1, 1‐bis‐(carboxymethylthio)‐1‐arylethanes derivatives showed good inhibitory action against acetylcholinesterase (AChE) butyrylcholinesterase (BChE), and human carbonic anhydrase I and II isoforms (hCA I and II). AChE inhibitors, interacting with the enzyme as their primary target, are applied as relevant drugs and toxins. Many clinically established drugs are carbonic anhydrase inhibitors, and it is highly anticipated that many more will eventually find their way into the market. The novel synthesized compounds inhibited AChE and BChE with Ki values in the range of 0.64–1.47 nM and 9.11–48.12 nM, respectively. On the other hand, hCA I and II were effectively inhibited by these compounds, with Ki values between 63.27–132.34 and of 29.63–127.31 nM, respectively.